Evolution of the milk value chain in Colméia - TO / Brazil and its interactions with the territory (Desenvolvimento em Questão, 2025)
The objective of the was to describe the evolution of the milk value chain in Colméia and its interactions with the territory. Secondary data collection involved bibliographic and documentary research. Primary data were collected through 43 semi-structured interviews conducted using non-probabilistic sampling with the main actors in Colméia's milk value chain, based on the theoretical framework of GVCs. It was observed that the milk value chain and the municipality's development are interconnected, with agriculture and livestock playing fundamental roles in Colméia's growth. The milk value chain emerged alongside the settlement and maintained modest, artisanal, and informal production for decades. In the second half of the 1990s, the first dairy plants were formalized, paving the way for two significant leaps in milk production in the following decades. The activity remains essential to the local economy, generating employment and income, although it faces important bottlenecks. Further studies are needed to address other aspects of the sector and explore the gaps that persist.
Keywords: family farming; milk value chain; development; economy; dairy industry